PENGARUH HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pelanggan Freshasan Cabang Banjarsari Selatan Semarang) - Pratiwi, Oktaria Diyah; Hidayat, Wahyu; Prabawani, Bulan (Jurnal Ilmu Administrasi Bisnis, 2016)
AbstractAlong with the development and progress of time resulted in increasingly tight competition among companies, so one way to enhanced the competitiveness of a company is to delivered products that have high quality and able to meet consumer desired, affordable price and attractive promotions. The purpose of this study was to determined the effect of pricing, promotion, and quality of service on purchasing decision on Freshasan fruit soup branch Banjarsari Selatan Semarang.The population in this study are all consumer who ever bought a Freshasanâ€™s fruit soup branch Banjarsari Selatan Semarang, with a sample size of 100 respondents with a sampling technique â€œpurposive random samplingâ€. The type of data used are primary data by using the method of data collection through questionnaires. An analysis tool used is linear regression analysis.The result of the study are : Price having influence on purchasing decision by 52,4%. Promotion having influence on purchasing decision by 42,9%. Quality of service having influence on purchasing decision by 53,4%. Together price, promotion, and service quality having influence on purchasing decision by 94,7%.Based on these result, it is suggested Freshasan need to keep the price to match with the quality of their products. Freshasan also have to increase the intensity of promotion, the quality of service needs to be maintained so that consumers satisfied and make repeat purchases.